2016
DOI: 10.1007/s10616-016-9997-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining impacts of ceranib-2 on the proliferation, morphology and ultrastructure of human breast cancer cells

Abstract: Acid ceramidases are enzymes with a vital role in metabolizing ceramide to sphingosine-1-phosphate that is an antiproliferative metabolite in the ceramide pathway. Inhibition of exogenous ceramides with ceramidase inhibitors lead to augmented ceramide levels in cells and in turn lead to cell cycle arrest and apoptosis. Our study aimed at targeting ceramide metabolic pathway to induce apoptosis in human breast cancer cell line (MCF7) and we examined the antiproliferative and apoptotic activities of ceranib-2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The hallmarks of apoptosis, which are cell shrinkage, membrane blebbing, chromatin condensation, nuclear fragmentation and mitochondrial swelling were detected via TEM in H460 cells. Further experiments by TEM showed that DU145, LNCaP and MCF-7 cells had similar morphological changes after ceranib-2 treatment (Kus et al 2015;Vethakanraj et al 2015;Vejselova et al 2016). Also vacuolization occurred in H460 cells after ceranib-2 application for 24 h. Ceramides are known to be important regulators of the crosstalk between apoptosis and autophagy (Gonzalez-Polo et al 2005;Young et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The hallmarks of apoptosis, which are cell shrinkage, membrane blebbing, chromatin condensation, nuclear fragmentation and mitochondrial swelling were detected via TEM in H460 cells. Further experiments by TEM showed that DU145, LNCaP and MCF-7 cells had similar morphological changes after ceranib-2 treatment (Kus et al 2015;Vethakanraj et al 2015;Vejselova et al 2016). Also vacuolization occurred in H460 cells after ceranib-2 application for 24 h. Ceramides are known to be important regulators of the crosstalk between apoptosis and autophagy (Gonzalez-Polo et al 2005;Young et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported that ceramide is intimately involved in cancer pathogenesis. Alterations in its metabolism are involved in regulation of cancer initiation, progression, and/or response to chemotherapeutic agents and radiation [ 16 , 32 , 33 ]. However, the clinical relevance of ceramide levels in patients with breast cancer remains unclear, due to lack of accurate measurement of ceramides in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…showed in 2016 that Ceranib-2, a small molecule acid ceramidase inhibitor, decreased viability of MCF7 cells in a dose and time dependent manner. The authors suggested that this effect was mediated by the mitochondrial apoptosis pathway through modulation of the mitochondrial membrane potential (Vejselova et al, 2016). …”
Section: Acid Ceramidase (Asah1)mentioning
confidence: 99%